The mTOR Pathway in Pluripotent Stem Cells: Lessons for Understanding Cancer Cell Dormancy - Bashar A. Alhasan (MDPI AG, 2021)
Currently, the success of targeted anticancer therapies largely depends on the correct understanding of the dormant state of cancer cells, since it is increasingly regarded to fuel tumor recurrence. The concept of cancer cell dormancy is often considered as an adaptive response of cancer cells to stress, and, therefore, is limited. It is possible that the cancer dormant state is not a privilege of cancer cells but the same reproductive survival strategy as diapause used by embryonic stem cells (ESCs). Recent advances reveal that high autophagy and mTOR pathway reduction are key mechanisms contributing to dormancy and diapause. ESCs, sharing their main features with cancer stem cells, have a delicate balance between the mTOR pathway and autophagy activity permissive for diapause induction. In this review, we discuss the functioning of the mTOR signaling and autophagy in ESCs in detail that allows us to deepen our understanding of the biology of cancer cell dormancy.